PEMBERDAYAAN UMKM KOTA BATAM MELALUI DIGITALISASI PEMASARAN E-COMMERCE UNTUK PERTUMBUHAN EKONOMI - Syahril Effendi; Tukino; Baru Harahap (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Ibnu Sina, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving economic growth, particularly inBatam City, which serves as a key trade and industrial hub. Despite their potential, many MSMEs struggle withmarket expansion due to limited access and knowledge of digital marketing. This study aims to examineempowerment strategies for MSMEs through the digitalization of e-commerce marketing to enhance theircompetitiveness and economic contribution. The approach includes structured training, mentoring, and technicalassistance to help MSMEs leverage e-commerce platforms, social media, and digital marketing techniqueseffectively. The training is conducted both in-person and online to ensure broad participation and maximizelearning outcomes. Through this initiative, MSMEs are equipped with essential digital skills that enable them toreach a wider customer base, streamline operations, and boost revenue. Findings from this study indicate thatdigitalizing e-commerce marketing significantly enhances MSME visibility, operational efficiency, and financialperformance. Key success factors include improving digital literacy among business owners, increasinggovernment support, and fostering collaborations with e-commerce platforms. Addressing these factors ensuresthat MSMEs can successfully integrate into the digital economy and remain competitive in an increasinglytechnology-driven market. A sustainable digital transformation strategy is essential, emphasizing continuousdigital skill development, access to necessary technological resources, and the establishment of a robust businessecosystem. By adopting e-commerce and digital marketing solutions, MSMEs in Batam City are expected to bemore adaptable to market trends, strengthen their business competitiveness, and make a greater contribution toregional economic growth.